Métodos consensuais de solução de conflitos trabalhistas e as empresas transnacionais - Do Val, Renata (2023)
The relationship evidenced in recent years between the Brazilian economic crisis, unemployment and high rates of demand for distributed and current labor lawsuits in the Judiciary are problems that increasingly require alternative forms of conflict resolution, whether through sustainable business management, which enables an adequate balance between capital and labor, either through consensual methods of conflict resolution, when already in place. It is necessary to rethink how to make the work environment sustainable, with respect to fundamental human rights, with better business management in this approach, which, in addition to reducing costs in terms of labor liabilities, makes the company more productive and profitable, especially in terms of regarding transnational companies – the largest holders of capital. However, preventive mechanisms for labor litigation may not always be sufficient, so it is necessary to rethink the ways to resolve conflicting issues through consensual methods, that is, mediation, conciliation, arbitration and, in some specific cases, extrajudicial agreements. The objective of this work is to identify, through a literature review, alternative methods of resolving labor disputes to resolve demands in this area of law, mainly from transnational companies.